ENT600 : e- Way drive-thru shopping at TESCO, Setia Alam / Aidatul Syamimi Mohd Tajudin, Nur Sharmila Sabri and Nurul Ayuni Mohd Azmi - Mohd Tajudin, Aidatul Syamimi; Sabri, Nur Sharmila; Mohd Azmi, Nurul Ayuni (2016)
This case study is done to analyse the shopping system at Tesco Setia Alam. This case study will analyse the problem face by shoppers and recommends the best alternatives for them to apply new system. There are some problems that shoppers face shopping at hypermarket. The problems were address from the process, technology and service oriented. It has been assumed that the problems come from weaknesses of the service system. The purpose to overcome the problems that faced by the service system method and it is also can ease up the shoppers. Development of computer-based system and android mobile application provides more benefits and influences that can shape and create the work culture more systematic and can change the administrative structure of an organization to be more quickly and effectively. The use of web-based application and android mobile application is not a new thing in the world of Information Technology (IT) nowadays.